Laporan Keuangan Lembaga Kemanusiaan Merujuk Pada PSAK 109 (Sebagai Kajian Untuk Laporan Keuangan Lembaga Nirlaba Syariah) - Yunida Een Friyanti (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
The development of sharia in Indonesia is not only followed by the Islamic financial institutions, but also began ogled by nonprofit organizations. Some humanitarian organizations are also changing its financial statements following the Islamic financial statements, such as Lembaga Amil Zakat has changed into nonprofit financial institution and used SFAS 109 as reference for financial statements, because there is no special provision for Sharia Nonprofit institution. In this article, the author tries to analyze changes in the financial statements which is using the system of Amil Zakat financial statements, and the possibility to do and is able to reflect the activities of the institution instead of Amil Zakat. As a result, the change in reporting format of SFAS 45 and SFAS 109 conducted by the Foundation for Fast Action Response not fully accurate as it needs confirmation on the Foundation certificate in order to purely applying SFAS 109. And the Financial Statements based on SFAS 109 is able to explain the activity of institutions rather than using the SFAS 45 the Foundation for Fast Action Response. It is expected to be input for the report of sharia-profit institutions